Assessing intracortical myelin in the living human brain using myelinated cortical thickness - Rowley, Christopher D.; Bazin, Pierre-Louis; Tardif, Christine L.; Sehmbi, Manpreet; Hashim, Eyesha; Zaharieva, Nadejda; Minuzzi, Luciano; Frey, Benicio N.; Bock, Nicholas A. (Frontiers in Neuroscience, 2015)
Alterations in the myelination of the cerebral cortex may underlie abnormal cortical function in a variety of brain diseases. Here, we describe a technique for investigating changes in intracortical myelin in clinical populations on the basis of cortical thickness measurements with magnetic resonance imaging (MRI) at 3 Tesla. For this, we separately compute the thickness of the shallower, lightly myelinated portion of the cortex and its deeper, heavily myelinated portion (referred to herein as unmyelinated and myelinated cortex respectively). Our expectation is that the thickness of the myelinated cortex will be a specific biomarker for disruptions in myeloarchitecture. We show representative atlases of total cortical thickness, T, unmyelinated cortical thickness, G, and myelinated cortical thickness, M, for a healthy group of 20 female subjects. We further demonstrate myelinated cortical thickness measurements in a preliminary clinical study of 10 bipolar disorder type-I subjects and 10 healthy controls, and report significant decreases in the middle frontal gyrus in T, G, and M in the disorder, with the largest percentage change occurring in M. This study highlights the potential of myelinated cortical thickness measurements for investigating intracortical myelin involvement in brain disease at clinically relevant field strengths and resolutions.